Impact of prosthetic heart valves on pregnancy in Bangladeshi women. (September 2019) - Ranjan, Redoy; Adhikary, Dipannita; Saha, Sanjoy Kumar; Mandal, Sabita; Hasan, Kamrul; Adhikary, Asit Baran
Background: This study evaluated pregnancy outcome in women with a prosthetic heart valve, especially with the oral anticoagulation therapy that must be weighed against the risk of intracardiac thrombosis. Methods: This multicenter, retrospective, cohort study was undertaken between January 2012 and June 2017. The principal maternal outcome variables included bleeding and thromboembolic complications, infective endocarditis, prosthetic valve thrombosis and heart failure. However, the main foetal outcome variables included miscarriage, mortality, preterm baby, warfarin embryopathy, low birthweight and the mode of delivery. Results: A total of 265 pregnancies in women with prosthetic heart valves were evaluated in two groups: Group I (n = 182) covers a mechanical valve, while Group II (n = 82) covers a bioprosthetic valve. The mean age of the patients was 25.2 ± 2.5 years and 24.5 ± 5.2 years in Group I and Group II, respectively. Approximately 80% of the patients had normal echocardiography findings. However, Group I (mechanical prostheses) has a higher incidence (11.54%) of thrombus formation in comparison with the bioprostheses. Hemorrhagic complications and spontaneous miscarriage were statistically significant (p⩽0.05) between the study groups. However, normal pregnancy outcome (91.57%) was significantly higher (p⩽0.05) in Group II compared to Group I (61.54%). Mean birthweight and mean APGAR score were found normal in both study groups. Only 2.75% of patients have warfarin embryopathy in Group I. Furthermore, comparison of SF-36 scores for HRQOL (Health-Related Quality of Life) before and after pregnancy were statistically insignificant among the study population. Conclusion: Proper antenatal care and early risk stratification are the fundamental measures to improve the maternal and foetal outcomes in a patient with a prosthetic heart valve.